Persistent Effects of Job Displacement: The Importance of Multiple Job Losses - Stevens, Ann Huff (Journal of Labor Economics, 1997)
This article examines the long-term wage and earnings losses of displaced workers using longitudinal data from the Panel Study of Income Dynamics. Consistent with previous research, the author finds that the effects of displacement are quite persistent, with earnings and wages remaining approximately 9 percent below their expected levels six or more years after displacement. She then shows that much of this persistence can be explained by additional job losses in the years following an initial displacement. Workers who avoid additional displacements have earnings and wage losses of 1 percent and 4 percent six or more years after job loss. Copyright 1997 by University of Chicago Press.